Costunolide Loaded in pH-Responsive Mesoporous Silica Nanoparticles for Increased Stability and an Enhanced Anti-Fibrotic Effect - Xia Niu; Xiaomei Wang; Bingyu Niu; Yanan Meng; Hongwei He; Yucheng Wang; Guiling Li (MDPI AG, 2021)
Liver fibrosis remains a significant public health problem. However, few drugs have yet been validated. Costunolide (COS), as a monomeric component of the traditional Chinese medicinal herb Saussurea Lappa, has shown excellent anti-fibrotic efficacy. However, COS displays very poor aqueous solubility and poor stability in gastric juice, which greatly limits its application via an oral administration. To increase the stability, improve the dissolution rate and enhance the anti-liver fibrosis of COS, pH-responsive mesoporous silica nanoparticles (MSNs) were selected as a drug carrier. Methacrylic acid copolymer (MAC) as a pH-sensitive material was used to coat the surface of MSNs. The drug release behavior and anti-liver fibrosis effects of MSNs-COS-MAC were evaluated. The results showed that MSNs-COS-MAC prevented a release in the gastric fluid and enhanced the dissolution rate of COS in the intestinal juice. At half the dose of COS, MSNs-COS-MAC still effectively ameliorated parenchymal necrosis, bile duct proliferation and excessive collagen. MSNs-COS-MAC significantly repressed hepatic fibrogenesis by decreasing the expression of hepatic fibrogenic markers in LX-2 cells and liver tissue. These results suggest that MSNs-COS-MAC shows great promise for anti-liver fibrosis treatment.